1977
DOI: 10.1104/pp.60.4.554
|View full text |Cite
|
Sign up to set email alerts
|

Polyribosome Formation in Relation to Cytokinin-induced Cell Division in Suspension Cultures of Glycine max [L.] Merr.

Abstract: We have investigated the relationship between cell proliferation and protein synthetic capacity in a cytokinin-requiring strain of cultured soybean ceUls (Glycine max IL.] Menf. cv. Sodffuri, of cotyledonary origin) in suspension culture. When transferred to a defined medium lacking cytokinin, very little cell division or cell enlrgement took place over the course of a 6-day culture period. Cells transferred to medium of the same composition, but containing 0.5 jM zeatin, exhibited rapid initial growth, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Our observation that 2,4-D (1 mg/l) added to pear cells after 6 days in the aging medium fails to induce cell division and protein synthesis is further indication that cytokinin synthesis might be suppressed. This hypothesis is supported by the observations of Maab and Klambt (21) (12).…”
Section: Discussionsupporting
confidence: 81%
“…Our observation that 2,4-D (1 mg/l) added to pear cells after 6 days in the aging medium fails to induce cell division and protein synthesis is further indication that cytokinin synthesis might be suppressed. This hypothesis is supported by the observations of Maab and Klambt (21) (12).…”
Section: Discussionsupporting
confidence: 81%
“…As far as we are aware, the present study is the first in which 16 Functional assays have suggested the involvement of cytokinins in the passage through several restriction points of the plant cell cycle. Cytokinins were found to be necessary for the entry of tobacco mesophyll protoplasts into S phase [10] and for the G2/M transition of tobacco and Glycine max suspension cultures [9,11]. Crowell and Salaz [33] have shown that the growth of tobacco BY-2 cells is inhibited by low concentrations of lovastatin, which inhibits the isoprenoid pathway that leads to the biosynthesis of the cytokinin side chain.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinins and auxins can interact both synergistically and antagonistically; for example, both are required to stimulate cell division in cultured tobacco pith tissues [7], but oppose each other in the control of shoot and root initiation in tissue cultures and in the maintenance of apical dominance [8]. Based on functional assays, cytokinins were suggested to be involved in the passage through several restriction points of the plant cell cycle [9][10][11], There is also evidence for the involvement of other plant hormones, such as abscisic acid [12], gibberellins [13], ethylene [14], and polyamines [15] in the regulation of cell division. Although the effects of phytohormones on plant growth have been studied extensively, not much is known about fluctuations in the levels of endogenous hormones during the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we know that newly synthesized proteins in culture are very different from the proteins of mesophyll cells, as their _u K patterns can be distinguished by monodimensional electrophoresis (5 (6,9), or for auxin and cytokinin (19). In fact, the observed modifications of enzyme activity often occur long after hormone application, frequently in high, nonphysiological concentrations.…”
Section: -D Protein Pattern In Protoplastsmentioning
confidence: 99%